Answer:
m=48
Step-by-step explanation:
Answer:
59
Step-by-step explanation:
ur welcome
Answer:
(-3,5)
Step-by-step explanation:
Please brainleist me
Answer:
x^2 -8x -5 = -3
x^2 -8x -2 = 0
We complete the square by:
1) Moving the "non X" term to the right:
x^2 -8x = 2
2) Dividing the equation by the coefficient of X²
The coefficient of x is 1 so we don't do anything
3) Now here's the "completing the square" stage in which we:
• take the coefficient of X
that is -8
• divide it by 2
-8 ÷ 2 = -4
• square that number
-4*-4 = 16
• then add it to both sides of the equation.
x^2 -8x +16 = 2 +16
That becomes
(x -4)^2 = 18
we take the square root of both sides:
(x -4) = sqr root (18)
x1 = sqr root (18) +4
AND
(x+4) = sqr root (18) -4
x1 = sqr root (18) +4 = 4.2426406871 + 4 = 8.2426406871
x2 = sqr root (18) -4 = = 4.2426406871 - 4 = .2426406871
Step-by-step explanation:
Find the common ratio. (The number you multiply or divide.) 3. Create a recursive formula<span> by stating the first term, and then stating the </span>formula<span> to be the common ratio times the previous term.</span>